Digital pathways to health engagement: Social-media use and telemedicine adoption intentions - Tara Qian Sun; Shiyu Cheng; Dong Guo; Xiaoming Zhou (Cultures of Science, 2026)
Telemedicine has emerged as an important component of digital health care, significantly advancing public health initiatives towards a more equitable and accessible health-care system. Meanwhile, social-media are widely recognized for their strong influence on shaping individuals’ intentions towards health-related behaviours, thereby transforming how people manage their health. Whether the purposes of using social-media are specifically related to telemedicine adoption intentions remains unclear. To address that gap, we investigated how distinct types of social-media engagement are associated with individuals’ telemedicine adoption intentions. Leveraging data from a cross-sectional survey in 2023 of 30,054 respondents in China, we found that all three purposes of using social media—information-seeking, social interaction and entertainment—are positively related to telemedicine adoption intentions. Moreover, positive interaction effects exist: eHealth literacy serves as a significant moderator in the relationship between social-media use and telemedicine adoption intentions. Our findings highlight the important role of social-media in supporting digital health engagement and provide theoretical and practical guidance for integrating eHealth literacy into public health strategies.